2020
DOI: 10.1111/jerd.12640
|View full text |Cite
|
Sign up to set email alerts
|

Color and translucency stability of contemporary resin‐based restorative materials

Abstract: Objective To determine color and translucency stability of present‐day resin‐based restorative materials. Materials and methods Disk‐shaped (1.0 × 10 mm) resin composites (Filtek Universal, 3M ESPE; Spectra ST, Dentsply Sirona; Gradia Direct X, GC America; Estilite Quick, Tokuyama; Harmonize, Kerr; ACTIVA Bioactive‐Restorative, Pulpdent) were prepared and divided into four staining groups (n = 5); coffee (55°C), grape juice (5°C), deionized water (25°C) and thermocycling (20 000 cycles, 5°C to 55°C with a 30‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
(41 reference statements)
4
25
0
1
Order By: Relevance
“…This is in correlation with previous studies which confirm that coffee has the highest staining potential [5,13,23]. Moreover, adhesive samples showed the same results in our and other studies [18,26]. According to the literature, coffee might produce more remarkable color changes of the material in comparison to other solutions (e.g., Coca-Cola) even though these solutions have similar color parameters [17].…”
Section: Discussionsupporting
confidence: 92%
“…This is in correlation with previous studies which confirm that coffee has the highest staining potential [5,13,23]. Moreover, adhesive samples showed the same results in our and other studies [18,26]. According to the literature, coffee might produce more remarkable color changes of the material in comparison to other solutions (e.g., Coca-Cola) even though these solutions have similar color parameters [17].…”
Section: Discussionsupporting
confidence: 92%
“…Their polish retention seems to be excellent 159 . However, it has been reported that the color stability of a few of the current universal composite resins is not ideal 161 …”
Section: Universal Composite Resinsmentioning
confidence: 99%
“…159 However, it has been reported that the color stability of a few of the current universal composite resins is not ideal. 161 Another characteristic of a few universal composite resins is the exclusion of Bis-GMA from the respective organic matrix. Since the introduction of the first composite resin, the composition of the organic matrix of composite resins has not changed considerably.…”
Section: Immediate Dentin Sealingmentioning
confidence: 99%
“…While there have been several studies of the color and translucency of dental resin-based composites (RBCs) for direct restoration as well as indirect dental ceramic materials [ 15 , 16 , 17 , 18 , 19 ], only limited information is available about those of 3D printable dental materials. Revilla-León et al measured the color of 3D printable dental materials and compared them with those of conventional acrylic resin-based interim materials [ 20 ].…”
Section: Introductionmentioning
confidence: 99%